Breastfeeding self-efficacy in Asia and Pacific: Scoping review - Artemio Morado Gonzales (Tehran University of Medical Sciences, 2020)
Background & Aim: Breastfeeding self-efficacy refers to a mother's perceived ability to breastfeed her new infant and is a salient variable in breastfeeding duration. This study aimed to review the current state of knowledge, including the predictors and interventions, and discuss relevant findings and gaps in the breastfeeding self-efficiency theory. Methods & Materials: Scoping review of peer-reviewed articles between the years of 2009-2019. Using the keyword breastfeeding, self-efficacy, and breastfeeding confidence, an extensive search of the PubMed, Scopus, and ProQuest databases was performed. A total of 1,200 publications were found, from which, after excluding duplication and non-related papers, only 34 publications were considered relevant to the subject and examined in-depth. This study utilized the data extraction form developed by the Joanna Briggs Institute. Results: There were various predictors of breastfeeding self-efficacy, such as fetal attachment, social support, and positive prenatal experience. Studies have claimed that educational programs through educational sessions, information packages, and peer education have a positive effect on breastfeeding self-efficacy and the duration of exclusive breastfeeding. Conclusion: To facilitate successful breastfeeding, health care institutions could promote interventions regarding positive breastfeeding experiences. The data suggest that breastfeeding self-efficacy moves beyond our current understanding of motherhood. However, this evidence is limited to the study conducted in western and developed countries, and results are coming from studies with limited sample size. To provide an assessment and information on Asian mothers in developing countries, data are needed to describe their experiences and to examine factors associated with breastfeeding self-efficacy in this population.